2007
DOI: 10.1016/j.compscitech.2005.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure evolution during thermal treatment of polyimide–fullerene composites as revealed by WAXS and SAXS

Abstract: The nanostructure formation in polyimide-fullerene composites during thermal treatment was investigated ''in situ'', by means of wide-angle (WAXS) and small-angle X-ray scattering techniques. The WAXS patterns of the PI composites do not reveal the presence of C 60 reflections. However, the PI/C 60 composite, obtained by adding the C 60 solution to the diamines-solution during the first step of the reaction (preparation of the polyamic acid, PAA), shows a maximum at small X-ray scattering angles. Results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…[6,[21][22][23][24][25] In this section, the indentation behavior of a PP/CNT nanocomposite, a PA6/LS nanocomposite and a polypropylene/boehmite (PA6/OS2) nanocomposite containing 2-2.2 wt.-% of nanoparticles (which represents 1D, 2D and 3D type of filler, respectively) has been compared.…”
Section: Indentation Behavior As a Function Of Filler Dimensionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…[6,[21][22][23][24][25] In this section, the indentation behavior of a PP/CNT nanocomposite, a PA6/LS nanocomposite and a polypropylene/boehmite (PA6/OS2) nanocomposite containing 2-2.2 wt.-% of nanoparticles (which represents 1D, 2D and 3D type of filler, respectively) has been compared.…”
Section: Indentation Behavior As a Function Of Filler Dimensionalitymentioning
confidence: 99%
“…These interactions depend, besides the polymer matrix, significantly on the filler type and dimensionality. [21][22][23][24][25] In this work, the microindentation behavior of different polymer nanocomposites is studied by means of a load vs. indentation depth recording microhardness testing machine [26][27][28] with the aim of determining the effect of the filler dimensionalities and the filler weight fraction on microhardness behavior of polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…The electron acceptor character of C 60 has also been emphasized by comparing the thermal behavior of the PI under study and the composite PI/C 60 , prepared by adding the C 60 to the diamine solution [9]. It has been shown that the composite presents a clear SAXS maximum that could be related to the three-dimensional location of the C 60 molecules within the PI/C 60 composite.…”
Section: Paa/c 60 Compositementioning
confidence: 99%
“…In a previous paper, we studied the influence of the fullerene C 60 on the nanostructure evolution of PI/C 60 during thermal treatment [9]. In that study, the pure polyimide PI was compared with the PI/C 60 composites prepared by adding the C 60 , either to the diamine (DAM) solution (route Ia), or to the dianhydride (DAN) solution (route Ib).…”
Section: Introductionmentioning
confidence: 99%
“…13 The in situ application of a wide range of X-ray techniques, using a variety of cells and reactors, has facilitated the study of many complex structural reorganization processes at the nanoscale. [14][15][16][17][18] In particular, time-resolved reaction data have provided insights into new intermediate species, reaction kinetics, and nanoparticle growth mechanisms. [8][9][10][11][19][20][21][22][23][24] Monitoring the dynamics of nanoparticle systems by SAXS presents a number of challenges related to the need for long data acquisition times.…”
Section: Introductionmentioning
confidence: 99%